Juvenile nasopharyngeal angiofibroma in a tertiary centre_ ten-year experience - Tang, I.P; Shashinder, S.; Gopala, K.G; Narayanan, P. (Singapore Medical Journal, 2009)
This is a retrospective study that aimed to examine the outcomes of patients presenting with juvenile nasopharyngeal angiofibroma (JNA) at a tertiary centre in Malaysia.